Enhancement of hydrogen clean energy production from greenhouse gas by in-situ hydrogen separation with a cobalt-silica membrane. (15th February 2023) - Ji, Guozhao; Yin, Xian; Fu, Weng; Kou, Xiaonan; Hotza, Dachamir; Wang, Yinxiang; Li, Aimin; Olguin, Gianni; Wang, Weijian
Abstract: Methane steam reforming is a representative reaction to convert carbon-rich fuel to carbon-free fuel. However, the thermodynamic equilibrium limits the conversion from methane to hydrogen. Separating hydrogen in-situ from hydrocarbon reforming reactions by inorganic membranes is an effective way to overcome the thermodynamic equilibrium, which improves the conversion of the reforming reactions and the efficiency of hydrogen production. Silica-based membrane, due to its size sieving effect, could separate hydrogen molecules from other larger gases at high temperatures, but the poor hydrothermal stability of silica in steam conditions remains a challenge for the application in hydrogen production. In this study, to improve the hydrothermal stability cobalt was doped in silica membrane precursors with varying ratios. After a series of characterizations by dynamic light scattering, Fourier Transform Infrared spectroscopy, X-ray diffraction, nitrogen adsorption and Scanning Electron Microscope, a cobalt-silica membrane with a cobalt/silicon ratio of 1/4 was fabricated by dip-coating technique. At 500 °C the membrane delivered helium permeance of 9.37 × 10 −8  mol m −2 s −1 Pa −1, helium/nitrogen perm-selectivity of 258.48, and helium/carbon dioxide perm-selectivity of 242.19. The membrane was then employed in methane steam reforming for in-situ hydrogen separation to enhance methane conversion and hydrogen production. Raising the reaction temperature favors the performance of the membrane reactor, but temperature over 550 °C was still challenging due to hydrothermal stability issue. Increasing reaction pressure from 0 to 0.3 MPa favored methane conversion, but pressure over 0.4 MPa led to concentration polarization. Steam to carbon (S/C) ratio of 3 was suitable to avoid nickel/alumina catalyst coking and methane dilution. Reducing the gas hourly space velocity (GHSV) ensured sufficient residence time for methane and favored methane conversion. At T  = 500 °C, Δ p  = 0.3 MPa, S/C = 3 and GHSV = 30 ml g −1 h −1, the membrane elevated the methane conversion from 45.36% (without membrane) to 83.71%. With a cobalt-silica membrane 4.32 ml min −1 of hydrogen was continuously produced with a purity of 82.12 vol% compared to 2.34 ml min −1 of hydrogen with a purity of 65.0 vol% in the case without a membrane. As expected, the micro-morphology of the cobalt-doped membrane after the 20-day steam reforming test showed little visible change in scanning electron microscope. The reduction of pore volume was only 15% as compared to 25% for pure silica material. This membrane demonstrated promising potential in the efficient production of hydrogen. Graphical abstract: Image 1